A bamboo-derived cellulose “high-speed rail” scaffold with gradient topology and temporal immunomodulation for tendon–bone interface regeneration - Yixuan Huang; Chen Chen; Hai Lan; Yichao Liu; Likun Liu; Heng Zhu; Lei Wang; Chenjian Peng; Hao Shu; Jiazhi Yang; Xin Liu; Luning Sun (Carbohydrate Polymers, 2026)

Enhancing performance and mitigating membrane fouling in an ICAMBR through poly aluminum chloride addition - Yumeng Yan; Zhenhao Wang; Luning Tian; Yang Liu; Min Xia; Yi Han; Shichan Qin; Feixiang Zan; Juan Mao; Xiaohui Wu; Xiejuan Lu (Journal of Environmental Chemical Engineering, 2026)

A Lorentzian decomposition and incremental learning framework for laser-induced breakdown spectroscopy of steels - Panyang Dai; Peichao Zheng; Jingjun Lin; Jinmei Wang; Guanghui Chen; Luning Li (Analytica Chimica Acta, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Association between venetoclax concentration and febrile neutropenia in acute leukemia: a retrospective analysis - Yuting Yan; Jin Sun; Yujiao Guo; Jieyu Sun; Yu Zhu; Luning Sun; Yongqing Wang (European Journal of Clinical Pharmacology, 2026)

Comparative toxicity of 6PPD and 6PPD-quinone on the gut-liver axis in zebrafish: Insights into microbiota dysbiosis and oxidative stress - Lipeng Liang; Hao Wang; Luning Cai; Jiaxin Liang; Xiaojun Niu; Xiaofei Song (Aquatic Toxicology, 2026)

The enrichment and source pathways of antibiotic resistance genes in leaf endophytes of organic vegetable mediated by light intensity - Yuzi Song; Jingxuan Liang; Luning Gong; Yu Wang; Di Zhang; Tailong Shi; Zhao Zhao (Plant and Soil, 2026)

Integrated multi-omics and physiological analyses reveal mechanism of enhanced gellan gum biosynthesis in an ARTP-induced Sphingomonas paucimobilis mutant - Ling Sun; Shiyi Chen; Yazhen Wang; Lei Sun; Zejian Wang; Yong Zhou; Ali Mohsin; Suyang Li; Luning Zhao; Afira Nayab; Wenjing Sun (Food Microbiology, 2026)

Unraveling synergistic radical and non-radical pathways in bromide and iodide-activated peroxymonosulfate systems for selective abatement of micropollutants - Jiaqi Ren; Ying Huang; Luning Wang; Boyuan Fan; Abdulaziz Al-Anazi; Lecheng Lei; Zhongjian Li (Environmental Research, 2026)

A hybrid assembly mechanism employs nonreducing polyketide synthase-like logic for partially reduced polyketide formation - Xianyan Zhang; Chuanteng Ma; Ziguang Deng; Xingtao Ren; Kaijin Zhang; Wenxue Wang; Luning Zhou; Yongchun Zhu; Guojian Zhang; Qian Che; Tianjiao Zhu; Hongan Long; et al. (Marine Life Science & Technology, 2026)
Fungal iterative type I polyketide synthases (iPKSs) are commonly classified into nonreducing (NR-), partially reducing (PR-), and highly reducing (HR-) polyketide synthases based on their assembly mechanisms and domain structures. These iPKSs have been considered functionally and evolutionarily distinct, characterized by clear boundaries. However, emerging genomic analyses suggest that the diversity of iPKSs in fungi is far from fully understood. Here, we describe the discovery and characterization of PbPKS1 from a marine-derived fungus Penicillium brocae HDN12-143, which exhibits an atypical domain organization arranged as KR-KS-AT-PT-ACP 1 -ACP 2 -CMeT-TE. Heterologous expression of PbPKS1 resulted in the production of two monohydroxybenzoic acids and two pyrones. In vivo and in vitro characterizations demonstrated that PbPKS1 has the capability to synthesize Cα-methylated partially reducing polyketides, yet involved a NR-PKS-like assembly mechanism, featuring a product template (PT) domain for aldol cyclization and a C-terminal thioesterase (TE) domain for product release. Phylogenetic analysis suggests that PbPKS1 belongs to a non-canonical PR-PKS (nPR-PKS) family, which is a minor grouping across the fungal kingdom, and possibly evolved from an NR-PKS through gene recombination. The discovery of nPR-PKS not only expands the diversity of iPKSs but also provides new insights into the evolutionary development of fungal iPKSs.

Antibiotic reduction enhances the aggregation of intracellular and extracellular resistance genes in the phycosphere - Yu Wang; Di Zhang; Yuzi Song; Jingxuan Liang; Luning Gong; Zhao Zhao (Journal of Environmental Chemical Engineering, 2026)

Novel antifungal talaroenamine L with unusual leptosphaeronyl moiety from marine-derived Talaromyces sp. HDN17-428 via HDACi elicitation - Komal Anjum; Luning Zhou; Khizar Hayyat; Xiaofei Huang; Jiaxiang Wang; Guojian Zhang; Tianjiao Zhu; Qian Che; Dehai Li (Natural Product Research, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Influence of genetic variants of imatinib on pharmacokinetics and recurrence-free survival in postoperative patients with gastrointestinal stromal tumor - Luning Sun; Mingqing Xu; Qiang Zhang; Yi Liu; Qiongye Huang; Jianghao Xu; Fengyuan Li; Hao Xu; Yongqing Wang (European Journal of Clinical Pharmacology, 2025)

Impact of phosphorus on the transfer of extracellular antibiotic resistance genes in water-sediment systems - Di Zhang; Jingxuan Liang; Yu Wang; Chao Xing; Yuzi Song; Ce Wang; Zikuo Liu; Xiaobin Yang; Luning Gong; Huijuan Shi; Zhao Zhao (Journal of Environmental Chemical Engineering, 2025)

Biocontrol efficiency and multiple mechanisms of Bacillus velezensis BV07 against postharvest green mold on citrus fruit - Chenyang Zhu; Juanying Huang; Mengyue Wu; GuangHao Li; Xiaoshuang Xia; Luning Zhao; Mahmoud Salah; Xinghua Zhou; Yun Wang (Postharvest Biology and Technology, 2025)

Optimizing zonal management framework suitable for mountain ecosystems by linking landscape, ecosystem service capacities and bundles nested - Yunqi Hao; Yihe Lü; Hui Dang; Da Lü; Chenjun Du; Yi Wang; Luning Wang; Xiaofeng Wang; Xuan Li; Bojie Fu (Journal of Environmental Management, 2025)

Dual role of C60 in modulating oxygen vacancy and carrier dynamic: a novel strategy to enhance photothermal catalytic CO2 hydrogenation - Wanqing Zhang; Yaqin Wang; Zufeng Qiu; Luning Chen; Zhaoxiong Xie; Qin Kuang (Chemical Engineering Journal, 2025)

Fine mapping of a novel powdery mildew resistance gene PmDM8 derived from a cultivated emmer (Triticum dicoccum) - Yongbo Zhao; Feifei Ma; Junmei Wang; Meng Han; Xuanshuo Liu; Aimen Shafique; Luning Xiao; Xuebing Wang; Jianing Xu; Xingyu Wang; Yueli Bai; Yiming Chai; et al. (Theoretical and Applied Genetics, 2025)

Structure of family health and its association with obesity-related eating behavior and depressive symptoms: Insights from network analysis - Junxu Lin; Zijuan Ma; Haihui Chen; Haoxian Ye; Wei Wang; Weishi Lin; Luning Yin; Rui Zhang; Dongfang Wang; Yunge Fan; Fang Fan (Appetite, 2025)

Core-shell SERS nanoprobes for ROS detection and imaging during apoptosis - Luning Wang; Xueying Gao; Jinchi Han; Jiayu Yuan; Zhouping Wang; Xiaoyuan Ma (Food Bioscience, 2025)

Enhancing H2O2 synthesis in photocatalytic self-Fenton degradation of antibiotics by modulating surface hydrophobicity of Fe-doped g-C3N4 with ionic liquids - Hongjie Zhu; Yushuo Sui; Zirui Yao; Haitao Zhao; Minghui Li; Luning Zou; Yikai Yang; Hongguo Hao; Pengfang Zhang; Hui-Juan Wang; Yao-Yao Wang; Shirong Kang (Journal of Environmental Chemical Engineering, 2025)

Multifunctional dynamic chitosan-guar gum nanocomposite hydrogels in infection and diabetic wound healing - Luning He; Shuyi Xing; Weikang Zhang; Ying Wang; Yian Li; Jinghao Chen; Jinghai Zhang; Siling Wang; Qinfu Zhao (Carbohydrate Polymers, 2025)

Induction of insulin resistance in female mice due to prolonged phenanthrene exposure: Unveiling the low-dose effect and potential mechanisms - Lu Fang; Feifei Kong; Kunlin Ou; Luning Hong; Chonggang Wang; Xiaomei Tong (Environmental Research, 2024)

Improved nitrogen removal by optimizing the distribution of dissolved oxygen in a simulated constructed wetland system with embedding a water-sealed zone for polishing reclaimed water - Yu Zheng; Nan Zhang; Rongshe Zhang; Chenguang Li; Zhen Liu; Yingzi Guo; Luning Zhang; Qian Wang; Yuanyuan Li; Mohomed Salah; Hao Zheng; Fengmin Li (Journal of Water Process Engineering, 2024)

Phase transition behavior and mesophase aging phenomenon during liquid-state carbonization of FCC decant oil - Bin Lou; Jichang Zhang; Jun Li; Weichao Chou; Luning Chai; Lingyan Tian; Xiaofeng Wang; Xiaoqiao Huang; Dong Liu (Fuel, 2024)

Weather and time factors impact on online food delivery sales: a comparative analysis of three Chinese cities - Wang Yao; Hongying Zhao; Luning Liu (Theoretical and Applied Climatology, 2023)

The association between long-term exposure to outdoor artificial light at night and poor sleep quality among Chinese veterans: A multi-city study - Xinyi Sun; Jiping Tan; Yan Chen; Yuewei Liu; Guang-Hui Dong; Bo-Yi Yang; Nan Li; Luning Wang; Shanshan Li; Gongbo Chen; Yuming Guo (International Journal of Hygiene and Environmental Health, 2023)

The effect of movement speed on audiovisual temporal integration in streaming-bouncing illusion - Luning Wang; Liyue Lin; Yujia Sun; Shuang Hou; Jie Ren (Experimental Brain Research, 2022)

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Increased drought and atmospheric CO2 positively impact intrinsic water use efficiency but do not promote tree growth in semi-arid areas of northwestern China - Kanglong Lu; Ning Chen; Xiaowei Zhang; Jingru Wang; Minghao Wang; Salman Khan; Chun Han; Cankun Zhang; Shuyuan Wang; Luning Wang; Wenting Gao; Yongjing Liu; et al. (Trees, 2019)

Correction to: Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

Grey-matter volume as a potential feature for the classification of Alzheimer’s disease and mild cognitive impairment: an exploratory study - Yane Guo; Zengqiang Zhang; Bo Zhou; Pan Wang; Hongxiang Yao; Minshao Yuan; Ningyu An; Haitao Dai; Luning Wang; Xi Zhang; Yong Liu (Neuroscience Bulletin, 2014)

Kinetics of the aerobic co-metabolism of 1,1-dichloroethylene by Achromobacter sp.: a novel benzene-grown culture - Shizong Wang; Qi Yang; Luning Zhang; Yeyao Wang (Biotechnology Letters, 2014)

Analysis of recoverable waste heat of circulating cooling water in hot-stamping power system - Panpan Qin; Hui Chen; Lili Chen; Chong Wang; Xiaoxiao Liu; Xiaojie Hu; Luning Yu; Shikui Liu (Clean Technologies and Environmental Policy, 2013)

Positron Emission Tomography with Pittsburgh Compound B in Diagnosis of Early Stage Alzheimer’s Disease - Jianjun Jia; Binbin Sun; Zhe Guo; Jinming Zhang; Jiahe Tian; Hongchuan Tang; Luning Wang (Cell Biochemistry and Biophysics, 2011)

A mismatch process in brief delayed matching-to-sample task: an fMRI study - Xi Zhang; Lin Ma; Shunwei Li; Yuping Wang; Xuchu Weng; Luning Wang (Experimental Brain Research, 2008)

Distinctive conflict processes associated with different stimulus presentation patterns: an event-related potential study - Xi Zhang; Yuping Wang; Shunwei Li; Luning Wang; Shujuan Tian (Experimental Brain Research, 2005)

D-Galactose-caused life shortening in Drosophila melanogaster and Musca domestica is associated with oxidative stress - Xu Cui; Luning Wang; Pingping Zuo; Zhitao Han; Zhengyu Fang; Wenbin Li; Jiankang Liu (Biogerontology, 2004)